Pengembangan Soal Numerasi Berbasis Konteks Nilai Budaya Primbon Jawa - Agus Prasetyo Kurniawan; Mega Teguh Budiarto; Rooselyna Ekawati (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2022)
This study describes developing numeration questions based on the context of Javanese primbon cultural values are valid. The questions are developed using the first three of the ADDIE method, analysis, design, and development. The validity is focused on four aspects, instruction, contents, construct, and language. The validating questions are three items of numeration questions in the form of complex multiple-choice questions. The validators in this research are four experts from Mathematics Education and Test/Evaluation Development. Results of the study show that the numeracy questions based on the context of Javanese primbon cultural values are valid with a score of 0.82. The final product is the prototype II is built upon the expert notion.